Modernist reinterpretations: rethinking al-Qur’ān and as-Sunnah through the eyes of M. Arkoun and Al-Jabiri - Jamaludin, Najiah Athirah; Muhammad, Fatimah (IIUM Press, 2025)
This paper discusses the Arab modernists and their understanding of al-Qur’ān and as-Sunnah in the light of the thoughts of M. Arkoun and Al-Jabiri. The researchers seek to explore the narrative of M. Arkoun and al-Jabiri by focusing on their views of al-Qur’ān and as-Sunnah. This research is both theoretical and philosophical, and therefore, is qualitative and depends much on textual research. The resources include printed and online materials. To analyse the data, the researchers have adopted critical and analytical methods. The findings show that the Arab modernists like M. Arkoun and Al-Jabiri were among the Muslim intellectuals who were triggered and thus influenced by the crisis of European modernity that engulfed the Arab world. Unfortunately, in the modern period, these Arab modernists and other Muslim modernists have completely rejected classical methodologies, instead, they borrowed the Western methodologies to study al-Qur’ān and as-Sunnah, and even in validating aḥkām